Classification for Avian Malaria Parasite Plasmodium Gallinaceum Blood Stages by Using Deep Convolutional Neural Networks - Veerayuth Kittichai; Morakot Kaewthamasorn; Suchansa Thanee; Rangsan Jomtarak; Kamonpob Klanboot; Kaung Myat Naing; Teerawat Tongloy; Santhad Chuwongin; Siridech Boonsang (My University, 2021)
Abstract Background: The infections of an avian malaria parasite ( Plasmodium gallinaceum ) in domestic chickens presents a major threat to poultry industry because it cause economical loss in both quality and quantity of meat and egg productions. Deep learning algorithms have been developed to identify avian malaria infections and classify its blood stage development. Methods: In this study, four types of deep convolutional neural networks namely Darknet, Darknet19, darknet19_448x448 and Densenet 201 are used to classify P. gallinaceum blood stages. We randomly collected dataset of 10,548 single-cell images consisting of four parasite stages from ten-infected blood films stained by Giemsa. All images were confirmed by three well-trained examiners. Results: In the model-wise comparison, the four neural network models gave us high values in the mean average precision at least 95%. Darknet can reproduce a superior performance in classification of the P. gallinaceum development stages across any other model architectures. In addition, Darknet also has best performance in multiple class-wise classification, scoring the average values of greater than 99% in accuracy, specificity, sensitivity, precision, and F1-score. Conclusions: Therefore, Darknet model is more suitable in the classification of P. gallinaceum blood stages than the other three models. The result may contribute us to develop the rapid screening tool for further assist non-expert in filed study where is lack of specific instrument for avian malaria diagnostic.
Keywords: Plasmodium gallinaceum; Avian Malaria; Leucocytozoon; Blood smear; Plasmodium (life cycle); Haemoproteus; Digital Imaging for Blood Diseases